PENDEKATAN TEORI KEAGENAN PADA KINERJA KEUANGAN DAERAH DAN BELANJA MODAL (STUDI PADA PROVINSI DI INDONESIA) - Riri Zelmiyanti (JRAK: Journal of Accounting Research and Computerized Accounting, 2016)
This study aimed to explore the effect of the local government financial performance to capital expendituresin all provinces in Indonesia. Studies of capital expenditure has been done but still a few who try to connectwith the theory of agency. This study tried to give evidence that financial performance in the aspects ofregional autonomy, the effectivity ratio, Silpa, and revenue growth. Population of this research is 33provincial governments in Indonesia. Province financial reports for the period 2006-2010 are used as sampleof this study. Regression analysis is used as data analysis technique. The results showed that autonomy havenegative significant effect to capital expenditure. The effectiveness ratio did not have effect the capitalexpenditures. SILPA had no effect to capital spending. Revenue growth has significant negative effect oncapital spending.